(3GdbGehS GdeMjW hGdbGHhS GdhSjW GdLGeY deG PgH ef cdGe GdYQH TeGWjWs - (3GdajQhRBHGOj, eLO GdOjf , CHh WGgQ, eMeO Hf jYbhH EHQGgje, J (B817 (3g`s ((3ecI GdecQeIs)
(3ChdgG (B:s
(3GdMeO ddg efWb GdHdZGA HGddZi aj GdHhGOj hehOY GddSGf CdSf GddSf GdghGOjs
(3BNQgG (B:s
(3gPG BNQ GdbGehS GdeMjW hGdbGHhS GdhSjW YfjJ HJUfjag hJCdjag hJgPjHg hJQUjag hde Bd LgOG aj JdNjUg hEJbGfg QGLjG Cf jchf NGdUG dhLg Gddg hQVhGfg hbO jSQ Gddg EJeGeg dg HefRdj Ydi GdUaG HecI GdeTQaI JLGg GdcYHI GdeYXeIs
(3efbhdI ef fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 46s
(3eYLe GdeDdajf(B: 3 / 776s
(3cTa GdXfhf(B: 2 / 1306s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs